The Relationship Between Job Demand And Emotional Intelligence With Burnout Among Factory Employees In Jepara - Diana Tria Ningrum; Nugraini Aprilia (International Journal of Science and Environment (IJSE), 2025)
Burnout is a form of psychological distress due to prolonged stress characterized by physical, mental, and emotional exhaustion involving factors such as job demand and emotional intelligence. The purpose of this study is to analyze the relationship between job demand and emotional intelligence with burnout in factory employees in Jepara. This study uses a quantitative research method using quantitative correlation research. The data collection technique used in this study is accidental sampling with a sample of 92 factory employee respondents in Jepara. The results of the analysis that job demand has a significant effect on burnout p of 0.031 (p <0.05) with rx1y 0.226. Meanwhile, emotional intelligence also has a significant effect on burnout p of 0.034 (p <0.05) with rx1y 0.221. Overall, both variables contribute effectively by 7.8% to burnout. The conclusion of this study is that there is a significant relationship between job demand and emotional intelligence with burnout. This means that employees with high job demands and emotional intelligence tend to experience burnout.